The Investigation of Lead Borate Glass Composites for Boron Neutron Capture Therapy Shielding - M. S. Ali; A. M. Abdelmonem; S. K. Elshamndy; G. M. Shoraiet; T. M. Mustafa; G. S. Hassan (PPIKSN-BATAN, 2022)
In this work, we studied the lead borate glass composites to optimize its shielding properties of thermal neutrons and gamma-rays for Boron Neutron Capture Therapy (BNCT) applications. Attenuation coefficients, half-value layer (HVL), and tenth-value layer (TVL) were measured for a broad range of gamma-ray energies, i.e., 356, 511, 662, 1173, 1274, and 1332 keV experimentally. Theoretical results using XCOM software show an agreement with the NaI(Tl) detector-based experimental measurements. The attenuation of collimated thermal neutrons, from Cf-252 source, was simulated using Monte Carlo-based code and compared experimentally with measurements by BF3 detector. A reasonable agreement between simulations and experiments was observed, suggesting that the shielding properties of lead borate glass (LBG) composites are monotonically increasing with the increasing of the lead and boron additives.